ANALISIS TEORI FRAUD TRIANGLE DALAM MENDETEKSI FINANCIAL STATEMENT FRAUD - Felicia Renata; Aan Marlinah (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to examine the influence of financial stability, external pressure, personal financial need, financial targets, nature of industry, ineffective monitoring, quality of external auditor, auditor change, and audit opinion on financial statement fraud. The sample used in this research is the manufacturing companies listed in Indonesia Stock Exchange (IDX) for the period 2019 to 2021. The sample was selected using purposive sampling method and the results obtained were 75 companies or 225 data. The data of this research was tested using logistic regression analysis. The result of the analysis shows that financial stability, personal financial needs, nature of industry, and quality of external auditor have an influence on financial statement fraud, while external pressure, financial targets, ineffective monitoring, auditor change, and audit opinion have no influence on financial statement fraud.